Determinants of Generation Z in Paying Zakat, Infaq, and Alms (ZIS) Online in the City of Surabaya - Rachmawati, Laela Nur; Canggih, Clarashinta (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
(ZIS) in Indonesia has enormous potential in obtaining fundraising, where the Muslim population dominates. However, the facts that occur in the field are that the maximum amount of ZIS fund collection has not been realized. The existence of online ZIS today is a form of innovation for zakat institutions in the era of technological development to be able to help encourage an increase in ZIS collection. This study aims to analyze the factors that influence Gen Z's interest in paying ZIS online. This study uses associative quantitative methods with Sem-PLS analysis and the Smart PLS analysis tool. Sampling used a purposive sampling technique with sample criteria namely Gen Z (15-25) years old Muslims in the city of Surabaya. The results of the study show that the accountability variable influences Gen Z's interest in paying ZIS online. If accountability has increased, the interest of Gen Z in the city of Surabaya in paying ZIS online has increased. Meanwhile, the variables of usability, ease of use, risk, and transparency do not affect Gen Z's interest in making ZIS payments online. The findings from this study are that it can be used to improve the online ZIS system so that fundraising can increase.